Rhabdomyolysis-Induced Acute Kidney Injury in Diabetic Emergency: Underdiagnosed and an Important Association to Be Aware of - Ami Amin; Bhavika Gandhi; Steven Torre; Alireza Amirpour; Jennifer Cheng; Mayurkumar Patel; Mohammad A. Hossain (Case Reports in Medicine)
Rhabdomyolysis is a potentially life-threatening clinical syndrome associated with muscle injury which can cause a leakage of intracellular contents, manifested from the range of being asymptomatic to a life-threatening condition causing acute kidney injury and severe electrolyte abnormalities. Rhabdomyolysis has been associated with both diabetic ketoacidosis (DKA) and hyperosmolar hyperglycemic nonketotic syndrome, though there is an increased association with rhabdomyolysis and acute kidney injury with hyperosmolar nonketonic state compared with patients with diabetic ketoacidosis. Common clinical manifestations are muscle pain, dark urine, and generalized weakness. The causes of rhabdomyolysis are broadly categorized into three groups: traumatic, nontraumatic exertional, and nontraumatic nonexertional. Here, we present a case of rhabdomyolysis-induced acute kidney injury in a patient with hyperosmolar hyperglycemic state. The patient was discharged on insulin and needed intermittent dialysis for two months. Our case highlights the importance of the rare association of rhabdomyolysis causing acute kidney injury in a diabetic emergency.